The SET and transposase domain protein Metnase enhances chromosome decatenation: regulation by automethylation - Williamson, Elizabeth A. (Oxford University Press, 2008)
Metnase is a human SET and transposase domain protein that methylates histone H3 and promotes DNA double-strand break repair. We now show that Metnase physically interacts and co-localizes with Topoisomerase IIα (Topo IIα), the key chromosome decatenating enzyme. Metnase promotes progression through decatenation and increases resistance to the Topo IIα inhibitors ICRF-193 and VP-16. Purified Metnase greatly enhanced Topo IIα decatenation of kinetoplast DNA to relaxed circular forms. Nuclear extracts containing Metnase decatenated kDNA more rapidly than those without Metnase, and neutralizing anti-sera against Metnase reversed that enhancement of decatenation. Metnase automethylates at K485, and the presence of a methyl donor blocked the enhancement of Topo IIα decatenation by Metnase, implying an internal regulatory inhibition. Thus, Metnase enhances Topo IIα decatenation, and this activity is repressed by automethylation. These results suggest that cancer cells could subvert Metnase to mediate clinically relevant resistance to Topo IIα inhibitors.